LKB1 regulates quiescence and metabolic homeostasis of hematopoietic stem cells - Gan, Boyi (2010)
The capacity to fine-tune cellular bioenergetics with the demands of stem cell maintenance and regeneration is central to normal development and aging and to organismal survival during periods of acute stress. How energy metabolism and stem cell homeostatic processes are coordinated is not well understood. LKB1 acts as an evolutionarily conserved regulator of cellular energy metabolism in eukaryotic cells and functions as the major upstream kinase to phosphorylate AMPK and 12 other AMPK-related kinases 1–3. Whether LKB1 regulates stem cell maintenance remains unknown. Here we show that LKB1 plays an essential role in hematopoietic stem cell (HSC) homeostasis. We demonstrate that ablation of Lkb1 in adult mice results in severe pancytopenia and subsequent lethality. Loss of Lkb1 leads to impaired survival and escape from quiescence of HSCs, resulting in exhaustion of the HSC pool and marked reduction of HSC repopulating potential in vivo. Lkb1 deletion impacted cell proliferation in HSCs, but not more committed compartments, pointing to context specific functions for LKB1 in hematopoiesis. The adverse impact of Lkb1 deletion on hematopoiesis was predominantly cell-autonomous and mTORC1-independent and involves multiple mechanisms converging on mitochondrial apoptosis and possibly down-regulation of PGC-1 coactivators and their transcriptional network which plays critical roles in mitochondrial biogenesis and function. Thus, LKB1 serves as an essential regulator of HSCs and hematopoiesis, and more generally, points to the critical importance of coupling energy metabolism and stem cell homeostasis.